High Performance and Stable All‐Inorganic Metal Halide Perovskite‐Based Photodetectors for Optical Communication Applications. Issue 38 (31st July 2018) - Bao, Chunxiong; Yang, Jie; Bai, Sai; Xu, Weidong; Yan, Zhibo; Xu, Qingyu; Liu, Junming; Zhang, Wenjing; Gao, Feng
Abstract: Photodetectors are critical parts of an optical communication system for achieving efficient photoelectronic conversion of signals, and the response speed directly determines the bandwidth of the whole system. Metal halide perovskites, an emerging class of low‐cost solution‐processed semiconductors, exhibiting strong optical absorption, low trap states, and high carrier mobility, are widely investigated in photodetection applications. Herein, through optimizing the device engineering and film quality, high‐performance photodetectors based on all‐inorganic cesium lead halide perovskite (CsPbI x Br3– x ), which simultaneously possess high sensitivity and fast response, are demonstrated. The optimized devices processed from CsPbIBr2 perovskite show a practically measured detectable limit of about 21.5 pW cm −2 and a fast response time of 20 ns, which are both among the highest reported device performance of perovskite‐based photodetectors. Moreover, the photodetectors exhibit outstanding long‐term environmental stability, with negligible degradation of the photoresponse property after 2000 h under ambient conditions. In addition, the resulting perovskite photodetector is successfully integrated into an optical communication system and its applications as an optical signal receiver on transmitting text and audio signals is demonstrated. The results suggest that all‐inorganic metal halide perovskite‐based photodetectors have great application potential for optical communication. Abstract : Photodetectors with a p–i–n structure, based on all‐inorganic metal halide perovskite CsPbI x Br3– x, are fabricated. Through optimizing the device structure and film quality, photodetectors simultaneously showing high sensitivity, fast response, and good long‐term stability are obtained. A prototype optical communication system based on the obtained photodetector as receiver is demonstrated to transmit text and audio data.